HETEROSIS STUDIES FOR EARLINESS AND SEED YIELD IN INDIAN MUSTARD (BRASSICA JUNCEA L. CZERN & COSS.) - Singh, KUMAR KANT; Singh, J.N.; SINGH, DHIRENDER; SINGH, RAJENDER (Annals of Agricultural Research, 2014)
Heterosis was examined for earliness, days to 50 per cent flowering, number of primary branches, number of secondary branches, number of siliqua on main axis, number of seed per siliqua, days to maturity, biological yield and seed yield from the material generated from 12 x 12 diallel mating design of Brassica juncea (L.) Czern & Coss. Negative significant heterosis considered desirable for days to 50 per cent flowering and days to maturity. Highest heterosis was found in crosses IC-199715X EJ-3 (-21.03), Krishna X DIRA-313-6 (-2.89), EJ-2 X IC-199714 (60.42), EJ-2X IC-199714 (70.0), EJ-IX Pusa Agrani (37.96), EJ-3X RH-30 (34.88), EJ-2X EJ-1 (151.6) and Pusa Agrani X EC-28 (179.75) for days to 50 per cent flowering, days to maturity, number of siliqua on main axis, number of seed per siliqua, biological yield and seed yield, respectively.